Test-retest reliability and construct validity of Inosen’s Silat Momentum Test - Inosen Lingsir Maghribi; Rony Syaifullah; M. Furqon Hidayatullah; Slamet Riyadi; Awan Hariono; Agung Nugroho (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Problem Statements: The kick in Pencak Silat has a magnitude called momentum, which requires a tool capable of measuring several variables based on the International System of Units (SI) in real-time. Nowadays, there are affordable and reliable sensor technologies to meet these needs. Purpose: The research aimed to design a test instrument that utilizes sensor technology to measure kick momentum in the sparring category of Pencak Silat following the applicable SI, and to test its reliability and validity. The resulting instrument is named Inosen’s Silat Momentum Test. Approach: This study followed Johnson and Nelson’s seven-test construction process. Twenty-four Pencak Silat athletes, consisting of 12 elite and 12 non-elite participants, were involved in the evaluation process. The test’s reliability was assessed by examining the correlation between the test and retest results. The construct validity test was conducted by comparing the results of the front kick tests of elite and non-elite Pencak Silat athletes. Data analysis was performed using Pearson correlation and independent t-tests using Minitab 21.4.1 software. Results: The results of the test and retest indicate a very high correlation (r = 0.923), demonstrating the consistent ability of Inosen’s Silat Momentum Test to measure kick momentum. The study found a statistically significant difference in the Inosen’s Silat Momentum Test scores (p < 0.05) between the elite fighter group (average score of 463.3 kg.m/s) and the non-elite fighter group (average score of 375 kg.m/s). The results indicate that Inosen’s Silat Momentum Test is an effective instrument for differentiating kick momentum based on fighter performance. Conclusions: Based on the findings, it is inferred that Inosen’s Silat Momentum Test is a reliable and valid instrument for measuring Pencak Silat kick momentum according to SI standards.